O Tensorze Przepuszczalności - D'Auriac, P.A. (Engineering Transactions, 1961)
The generalized Darcy law is assumed in the form, (1), Vi = PiCi. The object of the paper arc the assumptions for which the symmetry of the tensor Pij can be shown. The author’s opinion is that in the case of real soils the tensor pij is symmetric. By means of geometrical interpretation of the tensor and making use of the geometrical properties of the terrain, it is shown that the necessary and sufficient condition for the permeability to be isotropic is that the tensor Pi should have the form (3). Analogous argument leads to the form (4) for a soil where the direction of gravity forces is treated as special. This form is symmetric if «mirror symmetry» of the soil is assumed. The paper contains also a section concerning the permoability of a layered soil.